Long live the wasp: adult longevity in captive colonies of the eusocial paper wasp Polistes canadensis (L.) - Southon,Robin J; Bell,Emily F; Graystock,Peter; Sumner,Seirian (PeerJ PrePrints, 2014)
Insects have been used as an exemplary model in studying longevity, from extrinsic mortality pressures to intrinsic senescence. In the highly eusocial insects great degrees of variation in lifespan exist between morphological castes in relation to extreme divisions of labour, but of particular interest is the primitively eusocial orders. These species represent the ancestral beginnings of eusociality, in which castes are flexible and based on behaviour rather than morphology. Here we present data on the longevity of the primitively eusocial Neotropical paper wasp Polistes canadensis, in a captive setting removed of all environmental hazards. In comparison to other eusocial wasps’ P. canadensis had an average lifespan of 193±10.5 days, with one individual living longer than 450 days. Although this is shorter than most highly eusocial bee and ant queens. Natal colony variation does exist between P. canadensis colonies, possibly due to nutritional and genetic factors. This study provides a foundation for future investigations on the effects of intrinsic and extrinsic factors on longevity in primitively eusocial insects, as well as the relationship with caste and genome.
Keywords: Polistes; Polistes; wasp; longevity; eusocial; captive; polistes